STUDI PARAMETER FISIKA DAN KIMIA DAERAH PENANGKAPAN IKAN DI PERAIRAN PULAU HALANG KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR PROPINSI RIAU (STUDI KASUS PADA PENANGKAPAN IKAN DENGAN BUBU TIANG) - Muhammad Alfikri; Usman '; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Survey and measurement of aquatic environmental condition of Halang Island water was conducted in order to know the physical and chemical parameters in the Halang Island water. Measurement was conducted at three stations a long the Halang Island, and the data was collected has been analysis by multiple linear regression.The result of this observation for a environment parameter were as following temperatures 270C – 320C, current speed 0,2 m/s - 0,9 m/s, brightness 0,39 m - 0,45 m, salinity 15‰- 20‰, dissolved oxygen 1,8 mg/l – 2,1 mg/l and pH 5 – 6. Based analysis with multiple linear regression,the parameters of the water hasn't effect on catches indicated by the regression coefficient (R) of 0,0057 (close to zero) and R square value of 32,3%.According to the result analysis, can be concluded that the aquatic environment in the coastal area of Halang island was still suffientas habitat for living organisms and may be used for fishing activities.Keywords: Halang Island, Study physical and chemical parameters